BEBERAPA CATATAN TERHADAP KITAB-KITAB KARYA ULAMA MINANGKABAU PADA PERMULAAN ABAD XX - Pramono Pramono; Zahir Ahmad (Universitas Andalas, 2013)
The Kitabs (manuscripts and printed) of Minangkabau Scholars in the Early Twentieth Century are an important local sources in reconstructing the multicultural reconstruction of local Islamic. Era of the transmission of ideas and Islamic reformation movement in West Sumatra that began in the early twentieth century has given birth to two kinds of religious groups, namely